2015
DOI: 10.1007/s10620-015-3659-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Timed Barium Esophagogram and Esophageal Transit Scintigraphy Results in Achalasia

Abstract: Both TBE and ETS are useful modalities in assessing esophageal emptying and response to achalasia treatment. TBE and ETS results have a statistically significant correlation both pre- and post-treatment. We suggest that TBE could effectively replace ETS for the assessment of achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…12 TBE height is highly concordant with esophageal stasis and likelihood of failure of myotomy to palliate esophageal emptying. [12][13][14][15][16] Similarly, premyotomy TBE measures correlate with postmyotomy outcomes. 17 We and others have shown that improvement of esophageal emptying in the postmyotomy setting is ideally evaluated by TBE.…”
Section: Discussion Principal Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…12 TBE height is highly concordant with esophageal stasis and likelihood of failure of myotomy to palliate esophageal emptying. [12][13][14][15][16] Similarly, premyotomy TBE measures correlate with postmyotomy outcomes. 17 We and others have shown that improvement of esophageal emptying in the postmyotomy setting is ideally evaluated by TBE.…”
Section: Discussion Principal Findingsmentioning
confidence: 98%
“…TBE has replaced esophageal transit scintigraphy for this purpose because it is well tolerated and can provide an objective measure of esophageal emptying normalized to the patient. 13 It also provides this information with low levels of radiation, roughly one tenth to one fifteenth the dose of a computed tomography scan. TBE can also be a surrogate for repeated high-resolution manometry because TBE correlates with achalasia subtypes, 3 which are determinants of outcomes in achalasia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations can be used in a similar manner to TBS to assess the response to achalasia therapy. Posttherapy resolution of esophageal pressurization during rapid drink challenge performed as part of HRM, or bolus clearance as measured by impedance‐HRM, both correlate closely with barium stasis on TBS, and appear to be similarly predictive of long‐term symptom relapse 35–41 …”
Section: Utility Of Barium Esophagography Alongside Other Esophageal ...mentioning
confidence: 99%
“…In the event the total volume of the liquid consistency approaches 2 to 3 ounces while remaining mostly above the LES for longer than 5 minutes, then achalasia of the LES is suspected. This endoscopic screening methodology for detecting achalasia at the level of the LES is predicated upon an upright timed barium esophagram procedure [41,42]. In this case, the clinician makes a dysphysiological diagnosis of neurogenic gastroesophageal dysphagia characterized by signs consistent with achalasia of the LES.…”
Section: Les Achalasia Screeningmentioning
confidence: 99%